Influence of the compliance of a patient's body on the head taper fixation strength of modular hip implants. (July 2017) - Krull, Annika; Bishop, Nicholas E.; Steffen, Niels M.; Lampe, Frank; Püschel, Klaus; Morlock, Michael M.
Abstract: Background: The strength of the modular fixation between head and stem taper of total hip replacement implants should be sufficient to minimise relative motion and prevent corrosion at the interface. Intraoperatively the components are assembled by impaction with a hammer. It is unclear whether the effective compliance of the patient's body modifies the strength of the taper interface under impaction assembly. The purpose of this study was to assess the influence of the compliance of the patient's body on the taper fixation strength. Methods: Cobalt-chrome and ceramic femoral heads were assembled with titanium alloy stem tapers in the laboratory under impaction. Impaction forces were applied with a constant energy, defined by the drop height of the impactor, according to standard experimental procedure. The compliance of the patient was simulated in the laboratory by varying the stiffness of springs mounted below the stem taper. Pull-off forces between head and neck were measured to determine fixation strength. Findings: Decreasing spring stiffness had no effect on the applied peak impaction forces during assembly or on the pull-off forces. Pull-off forces showed no difference between metal and ceramic head materials. Interpretation: Pull-off forces and impaction forces were independent of the spring stiffness below the stem taper, indicating that the compliance of the patient has no effect on the taper fixation strength. Impaction testing in the laboratory can therefore be performed under rigid fixation, without accounting for the compliance of the patient. Highlights: Pull-off and impaction force for a fixed energy are independent of support stiffness. Metal and ceramic heads behave similarly. Head impaction in the laboratory can be performed with rigid stem fixation.